The Sociology of Art of Ignas Šlapelis - Gaižutytė, Žilvinė (Sociologija. Mintis ir veiksmas, 1999)
The article aims to analyze the sociological insights of Ignas Šlapelis, a Lithuanian art criticist, art historian and a pedagogue. The author argues that Ignas Šlapelis develops important sociological ideas to understand the cultural situation of Lithuania in the first half of the twentieth century. The author attempts to reconstruct the perspective of Ignas Šlapelis about the functions of art and its role in society. It is claimed that Ignas Šlapelis develops his sociology by discussing the role of art in the context of education. The author of the article suggests Ignas Šlapelis to be held as a founding father of Lithuanian sociology of art.
Keywords: Lithuanian sociology; history of sociology; sociology of art; Ignas Šlapelis